PERHITUNGAN VOLUME BATUGAMPING MENGGUNAKAN METODE PENAMPANG - Risky Y. Nainggolan; Juanita R. Horman (INTAN Jurnal Penelitian Tambang, 2021)
In the mining industry, it is very important to estimate the amount of mineral resources. This estimation aims to find out the volume of resources at the certain mining survey area. The estimation method used is the cross-section method, which is based on the rule of gradual changes and the rule of nearest point. The estimation using the rule of gradual changes shows that the total volume of limestone resources is 31,420 m³, and the volume of overburden is 27,572.6 m³. Meanwhile, the estimation using the rule of nearest point shows that the total limestone resource is 125,680 m³, and the overburden volume is 30,290 m³.